INDONESIA AND RUSSIA TRADE RELATIONS: SEARCHING FOR A PROSPECTIVE STRATEGIC PARTNERSHIP IN 2018 - Hendra Manurung (Sekretariat Jenderal DPR RI, 2018)
In March 2018, relations between Indonesia and Russia seem to be getting closer after agreeing to speed up the drafting of a new strategic partnership agreement in Moscow. While, a Plan of Consultation for 2017-2019 was signed by Ministers Retno L.P Marsudi and Sergey Lavrov aimed at intensifying dialogue between the two countries. Indonesia is important to Russia not only as a partner on international level, but as a country that plays a major role in the Association of Southeast Asian Nations. Under the Russia-ASEAN dialogue partnership, a road map for economic cooperation has been agreed upon and implemented. Over the past two decades, economic cooperation between Russia and Southeast Asia has lagged behind political cooperation. In order to strengthen closer trade and economic cooperation, it needs solutions to overcome barriers which, includes bureaucratic restrictions and the lack of information. This paper attempts to elaborate Indonesia-Russia trade relations as searching for a new strategic partnership. It employs qualitative research methods featuring descriptive analysis of the data on the bilateral relations within “The Framework of Friendly and Partnership in the 21st century”. Russia is important to Indonesia and vice versa in Indo-Pacific region as a promising and reliable partner in the development of its high-tech transfer and innovation in economy and defense cooperation. Di Maret 2018, hubungan Indonesia dan Rusia semakin dekat setelah penandatanganan draf perjanjian kemitraan strategis di Moskwa. Sementara Menteri Retno L.P Marsudi dan Sergei Lavrov menandatangani sebuah Rencana Konsultasi 2017-2019 bertujuan untuk mengintensifkan dialog kedua negara. Indonesia penting bagi Rusia bukan hanya sebagai mitra di level dunia, tetapi juga sebagai negara yang memiliki peran kunci dalam Perhimpunan Bangsa-bangsa di Asia Tenggara. Melalui hubungan kemitraan Rusia dan ASEAN, peta jalan untuk kerjasama ekonomi disepakati dan dilaksanakan. Lebih dari dua decade, kerjasama ekonomi antara Rusia dan Asia Tenggara tertinggal di belakang kerjasama politik. Saat ini merupakan waktu tepat menutup kesenjangan tersebut. Bagaimanapun, untuk menguatkan hubungan ekonomi dan perdagangan, diperlukan keseriusan untuk mengatasi berbagai hambatan, termasuk keterbatasan birokrasi dan kurangnya informasi. Tulisan ini menjelaskan signifikan, didukung materi praktis dan mengupayakan penyelesaian pada persoalan yang muncul, serta tujuan yang jelas bagi hubungan ekonomi Indonesia dan Rusia. Penelitian ini menggunakan metode riset kualitatif didukung analisa data deskriptif pada hubungan bilateral dalam “Kerangka Persahabatan dan Kemitraan di Abad 21”. Rusia penting bagi Indonesia demikian sebaliknya dalam mewujudkan stabiilitas kawasan Indo-Pasifik sebagai mitra yang dipercaya dan menjanjikan dalam alih teknologi dan inovasi technology di sector ekonomi dan kerjasama pertahanan